When Sophie's feelings are really, really hurt - Bang, Molly (Blue Sky Press, an imprint of Scholastic Inc., 2015)
Sophie's is hurt when the other children laugh at her painting of her favorite tree--but when she explains her painting everybody understands what she was trying to do.